2023
DOI: 10.1002/pld3.530
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous CAS9 editing of cpSRP43, LHCA6, and LHCA7 in Picochlorum celeri lowers chlorophyll levels and improves biomass productivity

Anagha Krishnan,
Melissa Cano,
Devin A. Karns
et al.

Abstract: High cellular pigment levels in dense microalgal cultures contribute to excess light absorption. To improve photosynthetic yields in the marine microalga Picochlorum celeri, CAS9 gene editing was used to target the molecular chaperone cpSRP43. Depigmented strains (>50% lower chlorophyll) were generated, with proteomics showing attenuated levels of most light harvesting complex (LHC) proteins. Gene editing generated two types of cpSRP43 transformants with distinct lower pigment phenotypes: (i) a transformant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
3
1
Order By: Relevance
“…These mutants showed reduced pigmentation due to incomplete, but still functional, light harvesting complexes (LHCs). This result contrasted both the authors’ expectations, and results found in a variety of other studies ( Baek et al., 2016 ; Caddell et al., 2023 ; Krishnan et al., 2023 ). The authors proposed two possible explanations, first that the mutants could have higher susceptibility to photodamage, second that the mutation strategies used resulted in off target gene editing with negative side effects.…”
Section: Photosynthetic Efficiency In Eukaryotic Microalgaecontrasting
confidence: 95%
See 1 more Smart Citation
“…These mutants showed reduced pigmentation due to incomplete, but still functional, light harvesting complexes (LHCs). This result contrasted both the authors’ expectations, and results found in a variety of other studies ( Baek et al., 2016 ; Caddell et al., 2023 ; Krishnan et al., 2023 ). The authors proposed two possible explanations, first that the mutants could have higher susceptibility to photodamage, second that the mutation strategies used resulted in off target gene editing with negative side effects.…”
Section: Photosynthetic Efficiency In Eukaryotic Microalgaecontrasting
confidence: 95%
“…Recently Krishan et al. found that the pigment content of Picochlorum celeri can be heavily reduced by CRISPR/Cas9 gene editing ( Krishnan et al., 2023 ). This work builds off previous studies done with Picochlorum celeri ( Krishnan et al., 2020 ; Cano et al., 2021 ), and focuses on the cpSRP43, LHCA6, and LHCA7 proteins.…”
Section: Photosynthetic Efficiency In Eukaryotic Microalgaementioning
confidence: 99%
“…Cultures were grown in a custom-built solar-simulating automated photobioreactor system (the ALGiSIM system, ALGi, Inc.) as described previously ( Cano et al, 2021 ) at a constant temperature of 33°C in 500-mL glass bottles bubbled with 2% CO 2 /air balance at a flow rate of 400 mL min −1 helping maintain a constant pH at ∼7.2. The solar day used had a maximum irradiance of 2,400 µmoles PAR m −2 s −1 at mid-day and represents a simulated summer day in Mesa, Arizona, excluding cloud cover, fog, rain, or other dynamic environmental fluctuations ( Krishnan et al, 2023 ). Cultures followed a daily dilution regime with a prescribed volume of culture (60% unless otherwise noted) dilution occurring 1 h before sunset.…”
Section: Methodsmentioning
confidence: 99%
“…The idea is not new ( Kok, 1953 ; Radmer Richard and Kok Bessel 1977b ) and has been used somewhat successfully to improve the solar-to-biomass conversion efficiency in mutants with truncated light-harvesting chlorophyll antenna (or tla ) ( Nakajima and Ueda, 1997 ; 2000 ; 1999 ; Polle et al, 2002 ; Polle, Kanakagiri, and Melis, 2003 ; Kirst et al, 2012 ; Jeong et al, 2017 ). In particular, mutants targeting genes of the chloroplast signal recognition particle (CpSRP) pathway affecting the assembly of LHC proteins display a smaller chlorophyll (Chl) antenna size, a higher Chl a/ b ratio, as well as a higher light intensity for the saturation of photosynthesis ( Kirst et al, 2012 ; Kirst and Melis, 2014 ; Jeong et al, 2017 ; Kirst et al, 2017 ; Krishnan et al, 2023 ). These concepts are actively being explored in microalgae and hold promising potential for verification in outdoor systems in the future.…”
Section: Introductionmentioning
confidence: 99%